Institutional Architecture for Financing Pan-Asian Infrastructure Connectivity - Biswa Nath Bhattacharyay; Madhurima Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2017)
Asia, particularly its major economies has witnessed slower growth in recent years. To make Asia more economically sustainable and resilient against external shocks to recover from the falling growth, most regional economies need to rebalance their export-oriented (mostly to advanced economies) production and growth towards Asian markets and regional demand, and trade-driven growth through increased intraregional infrastructure connectivity and regional economic integration. In 1992, a pan-Asian transport connectivity was initiated through, Asian Highway Network and Trans-Asian Railways Network. In 2015, an ambitious pan-Asian connectivity initiative, namely “One Belt, One Road” (ancient silk road) initiative has been proposed. This initiative plans to create an economic zone covering Asia, Europe and Africa. To successfully promote and finance greater physical connectivity, at the pan-Asian, sub-regional and national levels, Asia will require a strong and appropriate institutional framework for effective coordination, cooperation and collaboration among national, subregional, and region-wide institutions as well as other stakeholders. This paper discusses the prospects and challenges facing Asian connectivity as well as infrastructure financing needs in Asia. It also examines the nature and characteristics of existing and new institutions and the emerging role of regional and international institutions for enhancing Asian connectivity. Lastly, it proposes an institutional architecture consisting of new “Asian Infrastructure Coordination Facility (AICF)” involving major stakeholders for building a seamless pan-Asian connectivity through bilateral, regional and international cooperation, partnership and collaboration in infrastructure development.
Keywords: R10; R40; R42; 330; Asia; connectivity; hard and soft infrastructure; bilateral; regional and international institutions; inclusive and sustainable infrastructure; infrastructure financing; institutional architecture; financial instruments; bilateral and multilateral development banks